Lipid-Lowering Efficacy of Kuding Tea in Patients With Metabolic Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jiang, Zhonghui; Lu, Zhuqing; Wang, Tianyi; Wang, Yilian; Chu, Jianfeng; Chen, Keji; Gao, Zhuye (Frontiers in Nutrition, 2022)
Background: Kuding tea (KT), traditional tea material and widely used in China, has been found to have lipid-lowering effect in clinical and experimental studies. However, there has been no systematic review of the evidence on this subject. Methods: Eight electronic databases were searched from database inception until September 2021 for relevant randomized controlled trials (RCTs). We used the Cochrane Reviewer’s Handbook to assess the quality of the included studies. Weighted mean difference (WMD) and 95% confidence interval (CI) were used to measure the pooled effect size by random-effects model. Funnel plot, Egger regression test, and the Begg's test was used to assess publication bias. Results: Eight RCTs involving 716 patients were included in our meta-analysis. Comparing with the control group, KT group reduced serum total cholesterol (TC) levels (WMD: -0.56 mmol/L; 95% CI: -0.64, -0.47; I2 = 56.56%; P = 0.00), triglyceride (TG) levels (WMD: -0.30 mmol/L; 95% CI: -0.35, -0.24; I2 = 88.60%; P = 0.00), and low-density lipoprotein cholesterol (LDL-C) levels (WMD: -0.29 mmol/L; 95% CI: -0.37, -0.21; I2 = 89.43%; P = 0.00), but no significant effects on high-density lipoprotein cholesterol (HDL-C) (WMD: 0.07 mmol/L; 95% CI: -0.02, 0.16; I2 = 93.92%; P = 0.12). The results of sensitivity analysis were not altered after removing each study in turn. Subgroup analyses showed that KT intervention period was the source of heterogeneity. Following analysis, results revealed that long-term (> 4 weeks and < 8 weeks) use of KT increased HDL-C levels (WMD: 0.19; 95% CI: 0.13, 0.25). In addition, both the sensitivity analysis and subgroup analysis showed that our results were robust. No potentially significant publication bias was found from the funnel plot, Begg-Mazumdar correlation test and Egger regression test. Conclusions: KT supplementation can effectively improve lipid profile and KT is a promising approach to reduce blood lipid level in patients with metabolic disorders.